Introduction to relational database and SQL programming - Allen, Christopher (Mc GrawHill, 2004)
This text provides hands-on instruction to relational database design and management using Oracle examples. The proven format features step-by-step tutorials, end-of-chapter reviews, practice questions, key term lists, and lab projects.